The Effect of Probiotics on Childhood Constipation: A Randomized Controlled Double Blind Clinical Trial - M. Sadeghzadeh; A. Rabieefar; P. Khoshnevisasl; N. Mousavinasab; K. Eftekhari (International Journal of Pediatrics)
Background. Inconsistent data exist about the role of probiotics in the treatment of constipated children. The aim of this study was to investigate the effectiveness of probiotics in childhood constipation. Materials and Methods. In this placebo controlled trial, fifty-six children aged 4–12 years with constipation received randomly lactulose plus Protexin or lactulose plus placebo daily for four weeks. Stool frequency and consistency, abdominal pain, fecal incontinence, and weight gain were studied at the beginning, after the first week, and at the end of the 4th week in both groups. Results. Forty-eight patients completed the study. At the end of the fourth week, the frequency and consistency of defecation improved significantly (P=0.042 and P=0.049, resp.). At the end of the first week, fecal incontinence and abdominal pain improved significantly in intervention group (P=0.030 and P=0.017, resp.) but, at the end of the fourth week, this difference was not significant (P=0.125 and P=0.161, resp.). A significant weight gain was observed at the end of the 1st week in the treatment group. Conclusion. This study showed that probiotics had a positive role in increasing the frequency and improving the consistency at the end of 4th week.